Two Aspects of the “Individual” in Korean Lyric Poetry: Focusing on the Poems of Kim Sowol and Yoo Chihwan - Kim, Hosung (International Journal of Korean Humanities and Social Sciences, 2025)
This paper examines how the notion of the individual is poetically realized in modern Korean lyric poetry through a comparative reading of Kim Sowol and Yoo Chihwan. In Korea, modernity unfolded not as gradual cultural change but as a rupture shaped by colonization and liberation, making questions of subjectivity and identity especially acute in literature. Lyric poetry became a sensitive medium for registering shifts in interiority, affect, and world perception. Sowol’s poems construct a speaker who embraces separation from the world while actively reappropriating traditional sentiment; by organizing seemingly passive emotions into deliberate poetic structures, his work performs a politics of emotion, intervening in the world through inwardness. By contrast, Yoo confronts the absence of transcendence and treats nihilism as the starting point for ethical self-constitution; the self emerges as a resolute, responsible agent that shapes life without external guarantees. Reading these opposing yet complementary strategies together reveals a dynamic of convergence and divergence: while one turns inward to reclaim affective depth, the other expands outward through existential engagement. This dialectic shows how early modern Korean lyricism articulated and transformed the figure of the individual, offering a broader perspective on the evolving configurations of selfhood at the threshold of modernity.